2017
DOI: 10.1097/prs.0000000000003607
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Indications and Outcomes of Mastectomy in Transmen: A Prospective Study of Technical and Self-Reported Measures

Abstract: Background:Although transgender surgery constitutes a growing field within plastic surgery, prospective studies on masculinizing mastectomies are lacking. The objectives of the present study were to prospectively follow a cohort of transmen undergoing mastectomy to assess technical and self-reported outcomes and to evaluate surgical decision-making.Methods:Fifty-four transmen were recruited during a 10-month period at the Department of Plastic Surgery of the Centre of Expertise on Gender Dysphoria. Preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 19 publications
2
26
1
2
Order By: Relevance
“…The main goals of female-to-male chest reconstruction are to remove the breast tissue and excess skin and provide a masculine chest contour with strategically placed incisions to minimize scarring. 5 , 8 The NAC placement is a major factor in obtaining a masculine chest contour that is aesthetically pleasing to patients. It is important to not only reshape but also position the NAC to provide a more natural-looking male chest contour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goals of female-to-male chest reconstruction are to remove the breast tissue and excess skin and provide a masculine chest contour with strategically placed incisions to minimize scarring. 5 , 8 The NAC placement is a major factor in obtaining a masculine chest contour that is aesthetically pleasing to patients. It is important to not only reshape but also position the NAC to provide a more natural-looking male chest contour.…”
Section: Discussionmentioning
confidence: 99%
“…Important considerations for a successful surgery include scar placement, final positioning of the nipple-areola complex (NAC), and reshaping of the nipple and NAC. 8 Masculinization of the NAC has been specifically demonstrated to be a key aspect of chest reconstruction, significantly impacting the physical appearance and psychological well-being of transgender men. 13-26 There is debate within current literature surrounding which anatomical landmarks provide consistent measurements for nipple and NAC placement while also being applicable across varying body mass indices (BMIs).…”
mentioning
confidence: 99%
“…As expected, there were several differences in treatment preferences between the aM and aF groups, e.g., regarding top surgery. Feminizing hormonal treatment may cause satisfying breast growth (Coleman et al, 2012), and masculinizing chest surgery is widely observed to be of high priority for many aF individuals early in their social transition to facilitate being perceived publicly according to gender identity and to alleviate body dysphoria (van de Grift et al, 2017). Fewer aF than aM were certain that they wanted external genital surgery, consistent with expectations of surgical complications or unsatisfactory results being a common motive for not wanting surgical treatment (Beek et al, 2015) and that complication and revision rates for genital surgery are higher for masculinizing procedures (Pan & Honig, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review, gender affirming hormonal therapy improved quality of life and sexual function as well as decreased gender dysphoria and psychiatric morbidity for 72-80% of the patients (Murad et al, 2010). Gender affirming surgery of primary and/or secondary sex characteristics has been shown to alleviate gender dysphoria, raise the chances of being perceived according to gender identity, and improve quality of life (van de Grift et al, 2018) as well as global functioning (Johansson et al, 2010), although studies generally have low response rates and few participants. In Swedish treatment guidelines for so-called "top surgery" (The National Board of Health & Welfare, 2015), breast augmentation is a possibility for aM individuals after a year of potential hormonal treatment, and aF individuals may request mastectomy or masculinizing chest surgery.…”
Section: Introductionmentioning
confidence: 99%
“…For inclusion in our systematic review to identify studies that detail the development or evaluation of a patient decision aid for gender dysphoria or gender affirming treatment options, we used the population, intervention, control, outcomes, study design (PICOS) method (31). Our population of interest was persons experiencing gender dysphoria due to "distress resulting from a marked incongruence between the assigned gender and experienced gender" (32) or self-identify as TGD because their gender identity does not correspond with their phenotypic sex (33). We did not include persons with differences of sex development for whom chromosomal, gonadal, or anatomic sex development is atypical or ambiguous and have to decide on genital surgery (34).…”
Section: Inclusion Criteriamentioning
confidence: 99%